Dinamika Public Relations dalam Komunikasi Korporat di Indonesia Pasca Pandemi Covid-19 - Marlinda Irwanti; Siska Armawati Sufa; Miftahol Horri; Agustin Mulyono; Ivendriana Aprillia (JIKA (Jurnal Ilmu Komunikasi Andalan), 2021)
The ability of corporate PR practitioners to be able to manage relations with internal publics is a prerequisite for building good relations with external publics. In advancing their profession, corporate PR practitioners must be able to strategically manage management roles, communicate values to top management, advise executive leadership, and achieve internal stakeholder support for corporate communication activities. This paper aims to photograph the dynamics of Public Relations in corporate communication in Indonesia after the COVID-19 pandemic. The existence of the COVID-19 pandemic has made the public place trust and credibility in the first place when accessing information. Leaders in corporate communications act as catalysts and spokespersons on behalf of the organization. Public Relations needs to study more about messages if they need to be conveyed by leaders and messages that can be conveyed by Public Relations. In corporate communication after this pandemic, PR needs to make empathetic communication a principle in communicating. It is very important for a PR person to be able to convey messages transparently, clearly, and according to the public's needs while still prioritizing empathy. The researcher hopes that this article can be a reflection for PR people in Indonesia who carry out corporate communication activities in their daily lives.